Smart information desk system with voice assistant for universities - Dabiah Alboaneen; Dalia Alsaffar; Amani Alqahtani; Lama Alamri; Amjad Alfahhad; Bashaier Alqahtani; Alyah Alateeq; Rahaf Alamri; Fatimah Almohammedsaleh (Institute of Advanced Engineering and Science, 2021)
This article aims to develop a smart information desk system through a smart mirror for universities. It is a mirror with extra capabilities of displaying answers for academic inquiries such as asking about the lecturers’ office numbers and hours, exams dates and times on the mirror surface. In addition, the voice recognition feature was used to answer spoken inquiries in audio responds to serve all types of users including disabled ones. Furthermore, the system showed general information such as date, weather, time and the university map. The smart mirror was connected to an outdoor camera to monitor the traffics at the university entrance gate. The system was implemented on a Raspberry Pi 4 model B connected to a two-way mirror and an infrared (IR) touch frame. The results of this study helped to overcome the problem of the information desk absence in the university. Therefore, it helped users to save their time and effort in making requests for important academic information.